A Multicenter, Randomized, Controlled, Clinical Trial Evaluating a Lyopreserved Amniotic Membrane in the Treatment of Venous Leg Ulcers - Yadwinder Dhillon; Lena Levine; Gregory Tovmassian; Alexander Reyzelman; Francisco Perez‐Clavijo; Francis Wodie; Shawn Cazzell; Allan Grossman; Lesly Robinson; Felix Sigal; Robert S Kirsner; Mher Vartivarian; et al. (Health Science Reports)
ABSTRACT Background Standard of Care (SoC) with multilayer compression therapy along with proper wound management, may not be sufficient to close all venous ulcers and needs advanced therapies. Methods In this multicenter, prospective, randomized, controlled, open‐label trial, 351 patients were screened, 200 were eligible and enrolled and were randomized 1:1 to LPM (lyopreserved cellular placental membrane) plus SoC or SoC alone for up to 12 weeks. Patients were enrolled between June 2018 and November 2020 at 30 sites across the United States. Outcome measures included complete closure of the index ulcer (primary), reduction in wound size, rate of closure, quality of life, and adverse events. Results ITT analysis revealed that wounds treated with weekly applications of LPM as an adjunct to standard of care, reduced in size significantly more than SoC alone, at the end of 4, 8, and 12 graft applications, indicating a faster progression to closure. There was a statistically 1.72 higher relative risk or 72% higher probability of wound closure with LPM compared to the SoC group during the study period for wounds with an initial size of 3–25 cm2. Use of LPM as an adjunct was able to close statistically larger‐sized wounds on average. There was also a statistically significant fivefold improvement in quality of life (overall physical symptoms and daily life) over baseline, in the LPM treated patients as compared to the control group. Conclusion LPM and standard of care, significantly closed more venous leg ulcers and faster than standard of care alone and improved the quality of life for patients, suggesting that the use of aseptically processed LPM is a safe and effective treatment option in the healing of chronic venous leg ulcers. Trial Registration: ClinicalTrials.gov ID: NCT03629236, Study to Evaluate Safety and Efficacy of GrafixPL for the Treatment of Venous Leg Ulcers. (https://clinicaltrials.gov/study/NCT03629236).